Implikasi Yuridis Pembacaan dan Penandatanganan Akta Risalah e-RUPS yang Dibuat oleh Notaris - Ninik Alfiyah; Mohammad Saleh (Universitas Muhammadiyah Purwokerto, 2021)
The rapid development of information technology has been responded to positively by the Indonesian government for a long time, especially in organizing an electronic GMS, as regulated in Article 77 of Law Number 40 of 2007 concerning Limited Liability Companies. Guidelines for implementing e-GMS were only issued in 2020 because the Covid-19 pandemic threatens the economy and/or the stability of the country's financial system, this provision is in the form of POJK Number 16/POJK.04 / 2020. In Article 12 of the POJK, the implementation of e-GMS is obliged to be made in the form of a notary deed. This raises problems regarding the procedures for reading and signing deeds that cannot be done electronically because they are considered contrary to the Civil Code, the Law on Notary Position, and the ITE Law. The purpose of this research is to analyze the legal basis for the implementation of e-GMS and the minutes of the meeting and the legal consequences of reading and signing the e-GMS Notarial Deed electronically. This study uses a normative juridical research method. The results of the study explain that if the notary reads and signs the e-GMS deed electronically, it will have implications for the evidentiary power of the deed, which is equivalent to the letter under the bill because no regulation explicitly gives the notary authority in that field, so the advice given is e. -RUPS can be conducted electronically, however, the minutes of the meeting are made by the minutes of the meeting, and a copy is given to a notary so that the deed is in the form of a deed of partij and not a deed of relaas. Keywords: legal implications, reading and signing of the deed, e-GMS